Boosting BCG vaccination with MVA85A down-regulates the immunoregulatory cytokine TGF-beta1. - Fletcher, H; Pathan, A; Berthoud, T; Dunachie, S; Whelan, K; Alder, N; Sander, C; Hill, A; Mcshane, H (2008)
In clinical trials recombinant-modified vaccinia virus Ankara expressing the Mycobacterium tuberculosis antigen 85A (MVA85A) induces approximately 10 times more effector T cells than any other recombinant MVA vaccine. We have found that in BCG primed subjects MVA85A vaccination reduces transforming growth factor beta 1 (TGF-beta1) mRNA in peripheral blood lymphocytes and reduces TGF-beta1 protein in the serum, but increases IFN-gamma ELISPOT responses to the recall antigen SK/SD. TGF-beta1 is essential for the generation of regulatory T cells and we see a correlation across vaccinees between CD4+CD25hiFoxP3+ cells and TGF-beta1 serum levels. This apparent ability to counteract regulatory T cell effects suggests a potential use of MVA85A as an adjuvant for less immunogenic vaccines.